APLIKASI CAMPURAN AUKSIN NAA DAN IBA PADA PERTUMBUHAN DAN HASIL UBIKAYU - Setiya Wati, Tri Agus; Yusnita, Yusnita; Asmara, Sandi; Karyanto, Agus; Widyastuti, Raden Ajeng Diana (JURNAL AGROTROPIKA, 2025)
The growth and production of cassava can be increased through various efforts, including the use of superior varieties, fertilization, the addition of organic materials, and the application of growth regulators (PGR). Naphthaleneacetic acid (NAA) and indole-3-butyric acid (IBA) are PGRs that have been widely documented to stimulate root initiation and development in cuttings. The application of aauxin mixtures on cassava cuttings followed by fertilization and the addition of organic materials is expected to improve the growth and yield of cassava. The aim of this experiment is to study the effects of the application of an NAA and IBA mixture (1:1) and the type of fertilizer on the growth and yield of the Garuda variety of cassava. This research is designed using a clustered randomized block method with three replications. The design used is factorial 2x3, consisting of two main treatment factors. The first factor is the combination of growth regulators NAA and IBA in a 1:1 ratio at three concentration levels, namely 0 ppm, 500 ppm, and 1,000 ppm. The second factor includes the type of fertilizer used, which is a single inorganic fertilizer and a combination of inorganic fertilizer with cow manure. Each experimental unit in this study consists of 10 cassava cuttings planted in an orderly manner with a planting distance of 1 meter x 1 meter between plants. The results of the experiment showed that the application of inorganic fertilizer produced plant growth and the number of productive roots equivalent to the use of inorganic fertilizer + cow manure. The application of a mixture of auxins NAA and IBA (1:1) at concentrations of 500 ppm and 1,000 ppm significantly increased the growth of shoots, the number and weight of productive roots of the Garuda variety cassava, but both treatments resulted in cassava growth and yield that were not different. Key words: Cassava, cow manure, growth, IBA, NAA, yield